A new genus of Macrosiphini Wilson, 1910 (1887) (Hemiptera: Aphididae) from Rhododendron in Turkey - Barjadze, Shalva; Özdemir, Işil (Zootaxa, 2014)
Rhododendraphis tuatayae gen. n., sp. n. living on Rhododendron sp. (Ericaceae) in Turkey is described based on apterous viviparous females. The new genus is morphologically most similar to Rostratusaphis Fang and Qiao, 2009, but differs in several important characters. Differences between the new genus and other aphid genera with a spinulose second tarsal segment living on Rhododendron spp. worldwide are described. Type specimens are deposited at the Natural History Museum of London (BMNH).